Deliberative Formulation of Papua Special Autonomy Policy - KATHARINA, RIRIS (UI Scholars Hub, 2018)
Formulation of Special Autonomy Policy (Otsus) of Papua is a unique process, since it was mandated by MPR Decree to be carried out in a participatory manner with a strict time limit. In its development, Otsus policy has not been able to resolve the conflict in Papua. This paper aims to analyse the formulation of Papua’s Special Autonomy policy as outlined in Law No. 21/2001 based on deliberative public policy theories. This paper uses a qualitative approach with a case study, for which in-depth interviews were conducted with actors directly involved in policy discussions. The results show that the formulation of Papua Otsus has been made without involving Papuan people participation. The Assessment Team that drafted the autonomy law bill have failed to applied deliberative approach but a pseudo-participation. Subsequently, DPR did not provide the appropriate deliberative rooms for the discussions of the draft law.